2020
DOI: 10.20471/acc.2020.59.s1.02
|View full text |Cite
|
Sign up to set email alerts
|

Voice Outcomes as a Results of Voice Therapy after Lobectomy and Thyroidectomy

Abstract: SUMMARY Voice disorders are among the most common complications of thyroid surgery. It is therefore advisable to continuously monitor and report the outcomes of voice rehabilitation among people who underwent thyroid surgery in order to recognize which specific clinical actions are necessary to give those patients the maximum chance to restore quality of life. The aim of this study was to examine the outcomes of voice therapy in 35 persons (26 women and 9 men) aged between 20 and 75 years after tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Figure 4 shows the potential rehabilitation strategies for the management of dysphonia in thyroid cancer survivors. In particular, voice therapy is a specialized form of rehabilitation that focuses on improving vocal function and is mainly used for dysphonia treatment [77]. A trained speechlanguage therapist can guide individuals through different voice exercises and techniques to optimize vocal cord coordination, breath support, and resonance [78].…”
Section: Dysphonia In Thyroid Cancer Survivorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4 shows the potential rehabilitation strategies for the management of dysphonia in thyroid cancer survivors. In particular, voice therapy is a specialized form of rehabilitation that focuses on improving vocal function and is mainly used for dysphonia treatment [77]. A trained speechlanguage therapist can guide individuals through different voice exercises and techniques to optimize vocal cord coordination, breath support, and resonance [78].…”
Section: Dysphonia In Thyroid Cancer Survivorsmentioning
confidence: 99%
“…Different studies have shown positive outcomes, including improvement in vocal cord function, vocal quality, and reduced voice-related distress, despite only moderatequality evidence supporting voice therapy after thyroid surgery [76]. In particular, voice therapy is a specialized form of rehabilitation that focuses on improving vocal function and is mainly used for dysphonia treatment [77]. A trained speech-language therapist can guide individuals through different voice exercises and techniques to optimize vocal cord coordination, breath support, and resonance [78].…”
Section: Dysphonia In Thyroid Cancer Survivorsmentioning
confidence: 99%